Brief report: Correlates of inpatient psychiatric admission in children and adolescents with eating disorders. (30th March 2015) - Hamilton, Matthew J.; Watson, Hunna J.; Egan, Sarah J.; Hoiles, Kimberley J.; Harper, Emily; McCormack, Julie; Shu, Chloe; Forbes, David A.
ABSTRACT: Objective: To examine the prevalence and importance of psychological, behavioural, and situational correlates of impending psychiatric inpatient admissions in children and adolescents with eating disorders. Method: The sample consisted of 285 patients (8–17 years, M  = 14.4, SD  = 1.49) with DSM‐5 eating disorders assessed between 2006 and 2013 from the Helping to Outline Pediatric Eating Disorders (HOPE) Project. The sample was split into two groups, those with ( n  = 38) and without ( n  = 247) impending psychiatric admission; Discriminant function analysis was used to examine correlates. Results: The prevalence of impending psychiatric admission was 13.3%. Suicidal ideation provided the greatest discriminating power, followed by eating pathology, depressive symptoms, anxiety, multiple methods of weight control, binge eating, and family functioning. Conclusions: Earlier recognition of comorbid symptoms in eating disorders in the community may reduce the number of young people with eating disorders who present needing critical psychiatric care.